Ethanol–biodiesel–diesel blends as a diesel extender option on compression ignition engines - Zöldy, Máté (Transport, 2011)
Increasing fuel demand, decreasing natural reserves and environmental consciousness have together led to testing and implementing new fuels and blending components of compression ignition engines. Biofuels are very commonly added to fossil fuels, mostly ethanol to gasoline and FAME to diesel. Harmonizing their properties with engines is a great challenge for automotive and oil industry. Increasing demand for diesel oil in Europe raised the question about the possibility of increasing the amount of bio extenders. There were and certainly there are a number of experiments aimed at substituting or blending diesel with other fuels. One group of such fuels makes bioethanol– biodiesel–diesel oil mixtures. The paper proposes a global overview on literature and presents the obtained results. The article explores the possibility of using bioethanol–biodiesel–diesel oil mixtures in vehicles and agricultural compression ignition engines. The main aspect of researches was to find blends substitutable for compression ignition engines. Investigations were made to determine the maximum volume of a renewable part thus reaching the same or similar power output with lowering emissions. The received results were used for environmental and economical investigations. The valorisation of the results shows that bioethanol–biodiesel–diesel blends fulfil the cetane number, viscosity and lubricity requirements for standard diesel. Practical measurements and engine tests show that the utilization of a new fuel decreases emissions from the engine. The results of agricultural feedstock calculation indicate that in Hungary the biofuel part of the investigated fuels can be produced from an overflow. First Published Online: 05 Oct 2011